PREVALENCE OF GINGIVAL DISEASES AMONG ANEMIC PATIENTS ATTENDING A DENTAL COLLEGE - . B, Reshmi; Malaiappan, Sankari; S, Arvind (International Journal of Psychosocial Rehabilitation, 2020)
Anaemia is a common and serious health disorder among females and all age groups, with anemia of chronic disease being the second most prevalent. It is an inflammatory disease of supporting tissues of the tooth caused by specific microorganisms. Response to bacteria and their products induce major vascular response, of fiery explanatory mechanism for the interactions between periodontal infections and a variety of systemic disease. Therefore, periodontal results in low grade systemic inflammation, which may cause lower number of erythrocytes and consequently lower hb concentration. The aim of this study was to assess the prevalence of periodontal status of the anemia patient in Chennai-based population. The study was conducted in Saveetha Dental College Chennai. 50 female outpatients were randomly selected for the study. Parameters like bleeding on probing, hemoglobin levels, age were assessed. The data collected were then put in spss software for statistical analysis. Moderate anemia patients had a high frequency of generalized gingivitis and mild anemia patients had generalized gingivitis. Within the limitations of the study, it can be safely deduced that a positive relationship exists between the hematological parameters and severity of chronic periodontal disease, suggesting that long-standing chronic periodontitis may lead to the development of signs of anemia.